2010
DOI: 10.1093/jpepsy/jsq084
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parental Expressed Emotion: Associations with Adolescent Depressive Symptoms Among Youth with Spina Bifida

Abstract: This modified measure of parental EE can be used in future pediatric research that focuses on precursors or outcomes of this important parenting construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, she did so at a slower pace than the research sample, indicating an overall delayed trajectory (i.e. ages 12, 15, 16; [PAQ]; Kelly et al, 2010; Table 1; SOSBMR; Anderson, Auslander, Jung, Miller, & Santiago, 1990). Nevertheless, despite reported gains in medical autonomy, Farah’s responses on the AMIS (Buran et al, 2006), a structured interview about her current level of autonomy, indicated that she relies on her family to manage her condition.…”
Section: Medical Autonomymentioning
confidence: 91%
See 2 more Smart Citations
“…However, she did so at a slower pace than the research sample, indicating an overall delayed trajectory (i.e. ages 12, 15, 16; [PAQ]; Kelly et al, 2010; Table 1; SOSBMR; Anderson, Auslander, Jung, Miller, & Santiago, 1990). Nevertheless, despite reported gains in medical autonomy, Farah’s responses on the AMIS (Buran et al, 2006), a structured interview about her current level of autonomy, indicated that she relies on her family to manage her condition.…”
Section: Medical Autonomymentioning
confidence: 91%
“…However, an interview with Amineh when Farah was 15 years old provides some context for this information: “Well, so far, she takes care of everything to do with herself, aside from changing her diaper, because I am extremely conscious about her and wanting her to be in good condition and never to have a skin infection. And so I go out of my way to take care of her and never allow her to have any issues regarding that” (PAQ; Kelly et al, 2010). During the year of this statement, Farah’s medical chart indicated that she had a skin breakdown in the “diaper area.” Therefore, Amineh may have restricted her daughter’s knowledge of her condition as well as her motivation to take responsibility for her own self-management by maintaining control over changing her diaper.…”
Section: Medical Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…First, some of the studies in this special issue are reports of findings for previously developed measures; thus, the measure development portions of the checklist could not be completed (even though the validation portions of the checklist were relevant). Second, the first author of this article is a co-author on two of the papers in this special issue (Kaugars et al, 2010;Kelly, Holmbeck, & O'Mahar, 2010); thus, these papers were not evaluated in this review (i.e., only 10 of the 12 papers in the special issue are reviewed here).…”
Section: The Evidence Base For Measures Reviewed In the Special Issuementioning
confidence: 99%
“…In partial support of the impact of NP deficits on parental depressive symptoms, researchers have found increased levels of psychosocial stress in parents of children with MMC compared to parents of children without a disability [21][22][23]. Vermaes et al [24] in a meta-analysis of factors associated with parental distress, identified variables that correlate with parent's psychological adjustment including: child factors, parent factors, family factors and environmental factors.…”
Section: Introductionmentioning
confidence: 99%